ATG‐Induced Accelerated Immune Senescence: Clinical Implications in Renal Transplant Recipients. Issue 4 (10th March 2015) - Crepin, T.; Carron, C.; Roubiou, C.; Gaugler, B.; Gaiffe, E.; Simula‐Faivre, D.; Ferrand, C.; Tiberghien, P.; Chalopin, J.‐M.; Moulin, B.; Frimat, L.; Rieu, P.; et al.
Abstract: Persistent ATG‐induced CD4 + T cell lymphopenia is associated with serious clinical complications. We tested the hypothesis that ATG induces accelerated immune senescence in renal transplant recipients (RTR). Immune senescence biomarkers were analyzed at transplant and one‐year later in 97 incident RTR −62 patients receiving ATG and 35 receiving anti‐CD25 mAb (α‐CD25). This consisted in: (i) thymic output; (ii) bone marrow renewal of CD34 + hematopoietic progenitor cells (CD34 + HPC) and lymphoid (l‐HPC) and myeloid (m‐HPC) progenitor ratio; (iii) T cell phenotype; and (iv) measurement of T cell relative telomere length (RTL) and telomerase activity (RTA). Clinical correlates were analyzed with a 3 year follow‐up. Thymic output significantly decreased one‐year posttransplant in ATG‐treated patients. ATG was associated with a significant decrease in l‐HPC/m‐HPC ratio. Late stage differentiated CD57 + /CD28 − T cells increased in ATG‐treated patients. One‐year posttransplant T cell RTL and RTA were consequently lower in ATG‐treated patients. ATG is associated with accelerated immune senescence. Increased frequency of late differentiated CD4 + T cell frequency at transplantation tended to be predictive of a higher risk of subsequent opportunistic infections and of acute rejection only in ATG‐treated patients but this needs confirmation. Considering pretransplant immune profile may help to select those patients who may benefit from ATG to prevent severe infections and acute rejection. Abstract : Analysis of immune senescence biomarkers at transplant and one year later in renal transplant recipients reveals that ATG is not only associated with accelerated immune senescence, b ut that increased frequency of late differentiated CD4+ T cells at transplantation in ATG‐treated patients tends to be predictive of a higher risk of subsequent opportunistic infections and acute rejection.